A Review Indonesian Policy on Agricultural Industrial Commodities - Shoffiyati, Peni; Noer, Melinda; Syahni Z, Rahmat; ., Asrinaldi (International Journal of Engineering and Technology, 2018)
Agricultural development is defined as an integral part of economic and society development as a whole which is implemented in a planned manner. The role of the Government is as a stimulator and facilitator, so that the economic activities of farmers can be optimized albeit the many problems faced. The purpose of this study is to see how the form of agricultural development policy and its implementation on agricultural industry commodities as well as to understand the problems to improve the policies and overcome the existing problems. The method used in this study is the systematic literature review. The results of the study put forward several policies on agricultural industry commodity related to price, macroeconomic, investmentand supply chain management. Problems in agricultural development include technological, institutional, marketing and information issues. Supply chain management policy becomes the most important policy because it has a more comprehensive scope covering raw material supply management, activities among supply chain actors, pricing on each supply chain actor, to providing the necessary investment in the supply chain process. Implementers of supply chain management policies include supply chain management actors from upstream to downstream. Improvements made are shortening supply chain path by providing a meeting point of various related parties ranging from farmers as producers, intermediary traders to end consumers. The ultimate goal is expected supply chain will be shorter, travel distribution becomes faster, sharing of information, management of technology and existence of institutional network among supply chain actors.Â
Keywords: Agricultural Development; Policy review; Supply Chain Management.